Investigation of InAlGaN/GaN HEMT Device with SiC Substrate and Cap Layer in Self Heating Resistance for Microwave Applications - Merza, Marwah; Mohamed, Khalid (Iraqi Journal for Electrical and Electronic Engineering, 2025)
The electrical and radio frequency (RF) characteristics of InAlGaN/GaN high electron mobility transistors (HEMTs)device with cap layer are presented in this work. In this work, Silicon carbide was used as a substrate for its excellentthermal conductivity. Here, the thermal model was used to investigate the simulation of temperature distribution at 300k.Moreover, the DC and AC performance characteristics of the device were investigated using Silvaco Atlas TechnologyComputer Aided Design TCAD simulator. The results showed that, the maximum obtained drain current that was 1.35A. In addition to, the RF parameters were extracted. The cut-off frequency ft is (73 GHz), the maximum oscillationfrequency fmax is (353 GHz), maximum stable gain (Gms) and maximum available gain (Gma) with a value of about(116 dB). The obtained results showed that the InAlGaN/GaN HEMT device based on SiC performance is suitable formicrowave applications.